P251 RAID Dx: the first test based on faecal microbiota to differentiate irritable bowel syndrome from inflammatory bowel diseases. (25th January 2019) - Amoedo, J; Ramió-Pujol, S; Bahí, A; Puig-Amiel, C; Oliver, L; Torrealba, L; Ibáñez-Sanz, G; Clos, A; Mañosa, M; Cañete, F; Marín, I; Torres, P; et al.
Abstract: Background: The irritable bowel syndrome (IBS) is a functional disorder affecting up to 20% of world population. So far, there is not a specific diagnostic test. Diagnosis is based on the characteristic symptoms systematized in the Rome IV criteria and excluding main organic diseases. However, the overlap of IBS symptoms with other intestinal diseases, such as inflammatory bowel disease (IBD), requires to complement Rome IV criteria with biological markers such as faecal calprotectin (FC). Nevertheless, IBS is still one of the main reasons of unnecessary colonoscopies. RAID-Dx is a new non-invasive method for positive IBS diagnosis and its differential diagnosis with IBD patients. This test is based on detecting the specific IBS bacterial signature on stool samples. The aim of this study was to evaluate the potential of RAID-Dx as a diagnosis tool for IBS in comparison to FC. Methods: RAID-Dx was tested in 39 IBS patients and 51 IBD patients recruited from 5 Catalan hospitals. IBS patients met Rome IV criteria and presented a colonoscopy without valuable macroscopic lesions. IBD patients had clinical (Harvey–Bradshaw Index >4 and Mayo Partial Index >1) and endoscopic activity (SES-CD> 0 and Endoscopic Mayo Index >0 points). A stool sample from each subject, prior to the realisation of the colonoscopy, was obtained to determine RAID-Dx and FC. Results: RAID-Dx shows a high potential to distinguish between IBS and IBD patients with a sensitivity of 88.2% for IBS and a specificity of 89.2% for IBD. In contrast, the sensitivity and specificity of the FC (pre-determined cut-off 50 μg/g) was 51.5% and 92.2%, respectively. These results represent a substantial increase of the Negative Predictive Value of the RAID-Dx (94.3%) compared with that obtained with FC (74.6%). In addition, FC is analysed with a cut-off point of 150 μg/g as a hypothetical situation of maximum contingency. There is a significant increase in sensitivity for IBS (81.8%); however, the specificity decreases to 84.3% for the diagnosis of IBD. Conclusions: RAID-Dx is an accurate marker to diagnose IBS with high sensitivity and specificity, which makes it a candidate to become the diagnostic method of IBS. The use of this new tool will allow to reduce 75% of the unnecessary colonoscopies from IBS misdiagnosed patients by FC and its associated costs, time and risks.